HUBUNGAN KEJADIAN PERDARAHAN POSTPARTUM DENGAN KARAKTERISTIK IBU BERSALIN DI RB HARAPAN KITA - Buntoro Indra Dharmadi (Jurnal BIMTAS: Jurnal Kebidanan Umtas, 2018)
Postpartum hemorrhage is a major cause of maternal mortality. The World Health Organization (WHO) estimated 800 women die each day from complications of pregnancy and childbirth. Approximately 99% of all maternal mortality occur in developing countries. Based on the Indonesian Demographic and Health Survey (IDHS) in 2012, Maternal Mortality Rate (MMR) in Indonesia reached 359 per 100.000 live births. This study aimed to find out the relationship between the incidence of postpartum haemorrhage with maternity mother characteristics which include parity, maternal age, distance of pregnancy, and anemia in Harapan Kita Maternity Hospital during the period of 2013-2017. Methods: This was an analytic study with cross sectional design. Population were all the mothers who gave birth in Harapan Kita Maternity Hospital during the period of 2013-2017. Of the total population, 43 cases were selected as sample using the total sampling method. Data obtained using secondary data with complete medical records as a criteria for inclusion, bivariate analyzis were peformed using chi square. Results: The results of this study indicate, most postpartum hemorrhage is caused by uterine atony (46.51%). For the characteristics that influence consists of ages between 20-35 years (55.90%), pregnancy ? 2 years (86.05%), parity 2-3 (53.50%) and those with Hb level ? 11 g/dl% (76.74%). The results of the statistical test chi square shows a mother's gestational age between 20-35 years and parity had a close relationship with the incidence of postpartum haemorrhage due to the rest of the placenta with p value = 0.032 (p <0.05) for the age and p value = 0.030 (p < 0.05) to parity. Conclusion: The conclusion obtained that there is a relationship between maternal characteristics based on age and parity with postpartum haemorrhage, and there is no relationship between maternal characteristics based on the distance of the pregnancy and Hb levels (anemia) with postpartum haemorrhage in Harapan Kita Maternity Hospital during the period of 2013-2017. Keywords : Maternity mother, Mother Characteristics, Postpartum hemorrhage